Défrichage et enfrichement en haute vallée du Cañar (Sud andin de l’Équateur) : l’empreinte de l’émigration paysanne sur un paysage agraire ? - Michel Vaillant; Marc Oswald (Revue de Géographie Alpine)
On the threshold of the 2Ist century, Ecuador fell into the darkest economic period in the history of its republic, the cause of which was a vast migratory movement abroad. In the high Andes valley of Cañar, the swiftness and extent of the movement seemed, in many ways, to be the precursory signs of an exodus and a return to nature of the environment. A decade later, the agrarian landscape shows a strange paradox : some sections of land, apparently abandoned to wilderness, suggest a progressive decline in agriculture, whereas others suggest the progression of a fodder front to higher altitudes. So what can we say about this landscape that shows a process of set-aside in some of its sections and cultivation in others ? What meaning can we give to the term ‘fallow’ with the mountains providing information on what appear to be antagonistic methods of agricultural development ? These are the questions dealt with in this article, with ‘fallow’ as the main thread. An analysis of the land, combined with the use of the agricultural history of the study area, helps to shed light on the reasons for the observed paradox and gives meaning to the relationships between types of fallow and agricultural dynamics, mobility and the process of social differentiation. Principal result : far from signifying abandonment, fallow land is visual proof in the landscape of the maintenance of agricultural activity by those who are unable to migrate or modernize their farms. This result invites us to revisit the notion of wasteland fallow (from an agro-economic point of view), in particular the need to understand the stakes and uses of the various tiered ecosystems and to understand the function of the different fallow lands assigned to them by the categories of farmers who take part in them.